Audiovisual Learning Videos on Cultural Themes to Stimulate Kindergarten Children's Language Development - Theresia, Theresia Ayu Wulandari; Didith Pramunditya Ambara; Maria Goreti Rini Kristiantari (Universitas Pendidikan Ganesha, 2024)
Changing learning activities from online to offline has several difficulties, where if children learn at home or are held online it is rather difficult to get children to concentrate. In addition, the lack of innovative learning media affects student learning outcomes. This study was conducted with the aim of developing an audio-visual learning video on the theme of culture, as well as analyzing the feasibility and effectiveness of audio-visual learning videos on the theme of culture to stimulate the language development of kindergarten children. The product was tested by 3 expert lecturers and 15 students. This research is a development research using the ADDIE model. Development research uses data collection methods with questionnaires and uses observation questionnaires (non-test). Data analysis techniques used quantitative descriptive analysis and inferential statistics. The results of the study found that the design of audio-visual learning videos received very good qualifications, the feasibility test of learning videos showed the results of learning videos developed were very feasible to use in learning, and the effectiveness of learning videos based on t-tests, where the hypothesis H0 was rejected and H1 was accepted. This means that learning videos are effectively applied to early childhood in kindergarten.